Element transport in the Taz River, western Siberia - Pokrovsky, Oleg S.; Manasypov, Rinat M.; Chupakov, Artem V.; Kopysov, Sergey G. (Chemical geology)
The riverine export fluxes of dissolved carbon, nutrient and metals from the land to the Arctic Ocean are fairly well quantified for five large Arctic rivers but remain virtually unknown for mid-sized Eurasian rivers, notably those draining through the permafrost zone. Because such rivers can most rapidly respond to on-going climate warming and permafrost thaw in the Arctic, their current hydrochemical composition and elemental yields are badly needed for judging the level of changes in the very near future. Towards quantifying the annual export fluxes and assessing the mechanisms of seasonal variability of river solutes, we monitored the pristine subarctic Taz River (Swatershed = 150,000 km2), which drains through boreal forest and peatlands in the discontinuous and continuous permafrost zone, on a weekly to monthly basis over a 3 year period. Based on seasonal pattern of riverine solutes (< 0.45 μm) and their dependence on discharge, 3 groups of elements were distinguished. These groups of solutes were consistent with several main sources of elements in the main stem of the Taz River such as deep groundwater, riparian zone and floodplain lake sediments, plant litter, mineral soil water, and peatwater from the peatlands. The 1st group was represented by dissolved inorganic carbon (DIC), specific conductivity, and some nutrients (NO3, NH4, Ntot and Si) and soluble elements that originated from groundwater and deep soil mineral horizons (Cl, SO4, Li, B, Na, Mg, Ca, Si, K, Rb, Mn, Co, Sr, Mo, Cs, Ba and W) and showed maximal concentration at the end of winter, before the spring ice-off. This group showed negative correlation to discharge. The 2nd group included dissolved organic carbon (DOC), low-mobile hydrolysates and organically-complexed trace metals (Al, Be, V, Ni, Y, Se, Zr, Nb, REEs, Hf, Pb and Th) which demonstrated maximal concentrations during the spring flood and autumn high flow and minimal values during winter. The concentration of these elements generally increased with water discharge, presumably due to their mobilization in the form of organic and organo-mineral colloids by surface flow through forest litter and via suprapermafrost flow from peatlands. And lastly, the 3rd group of solutes included macronutrients (P, N), Fe, Ti, Cr, Ga, Ge, As, Pb, and U which exhibited features of first two groups and originated from both surface and underground sources. This group showed the strong impact of autochthonous biotic processes in the river channel and soils of the watershed (nutrients, Si). Similar to other Arctic rivers, the spring flood (May and June) provided 30–40% of annual export for DOC, macronutrients and most major and minor solutes. The exceptions are DIC, Si, Ca, Mg and Fe which exhibited essential (30–40%) export during winter baseflow, whereas >70% of annual Mn flux occurred in winter. A number of elements present in the snowpack exhibited sizable (> 45%) export during spring flood (Zn, Cu, Pb, Cd, Sb and Cs). The 3 years mean export fluxes (yields) of dissolved components were comparable to or 30–50% lower than those of other large and medium sized Arctic rivers. This was due mostly to a lack of fresh unaltered rocks and a dominance of peatlands within the Taz River watershed. Elevated concentrations of redox-sensitive micro-nutrients (such as Fe and Mn) occurring during winter baseflow can be linked to disproportionally large floodplain zone of this river which can act, especially in the river's lower reaches, as a stratified lake thereby releasing high amounts of redox-sensitive elements from the sediments. The role of suboxic zones in the Arctic boreal riverine landscape may be more important than previously thought, and may allow explaining anomalously high concentrations of some metals (i.e., Mn) reported in Arctic Ocean surface waters. It is anticipated that climate warming in the region may increase the contribution of winter flow and enhance the export of soluble elements and some nutrients (such as Si, Mn and Co).